Phospholipid composition of chick brain during development - T.J. Siek; R.W. Newburgh (Journal of Lipid Research, 1965)
The phospholipid composition of chick embryo brain was examined over the interval 4–18 days of incubation. Phosphatidyl ethanolamine accounted for about 25% of the total lipid phosphorus during this interval, while phosphatidyl choline decreased from 70 to 50%. Sphingomyelin formed a relatively low fraction of the total phospholipid. The sum of inositol phosphatides and phosphatidyl serine was about 5%, with slight variation during the interval studied. A phospholipid resembling cardiolipin was detected. Its content increased to 4% during this incubation period.